The Sufficient and Necessary Conditions for the Poisson Distribution Series to Be in Some Subclasses of Analytic Functions. (5th May 2022) - Lashin, Abdel Moneim Y.; Badghaish, Abeer O.; Bajamal, Amani Z.
Abstract : In this paper, we introduce new subclasses of analytic functions in the open unit disc. Furthermore, the necessary and sufficient conditions for the Poisson distribution series to be in these new subclasses are found.